2006
DOI: 10.1158/1078-0432.ccr-05-1682
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Effects of Combined Epidermal Growth Factor Receptor and Vascular Endothelial Growth Factor Receptor-2 Targeted Therapy

Abstract: Purpose: Combination therapies that target the epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor (VEGFR) pathways, are being actively tested for the treatment of cancer. In evaluating combination strategies, the ideal combination would be one in which the treatments interact in a way that is synergistic with regard to antitumor effects. Here, we have evaluated the interaction between anti-EGFR antibody Erbitux (cetuximab) and anti-VEGFR2 antibody, DC101, in preclinical mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 30 publications
(45 reference statements)
2
80
0
1
Order By: Relevance
“…Preclinical studies confirmed a synergistic growth inhibition (Morelli et al, 2006;Tonra et al, 2006) and preliminary clinical data have already verified efficacy of the combination . The BOND II trial was a randomized phase II trial (combination of Cx and Bv with or without irinotecan), but it was sadly preliminary stopped due to poor accrual after inclusion of only 74 patients with irinotecanresistent mCRC (Table 3).…”
Section: Combination Of Targeted Therapiesmentioning
confidence: 79%
“…Preclinical studies confirmed a synergistic growth inhibition (Morelli et al, 2006;Tonra et al, 2006) and preliminary clinical data have already verified efficacy of the combination . The BOND II trial was a randomized phase II trial (combination of Cx and Bv with or without irinotecan), but it was sadly preliminary stopped due to poor accrual after inclusion of only 74 patients with irinotecanresistent mCRC (Table 3).…”
Section: Combination Of Targeted Therapiesmentioning
confidence: 79%
“…23,26 In addition, the combination of EGFR and VEGFR2 antagonists enhanced anti-tumor effect, which suggests EGFR and VEGFR2 co-targeted therapy has therapeutic potential in colon tumors. [27][28] In this article, we designed a bispecific antibody based on a known EGFR antibody and our VEGFR2 antibody. Its efficacy was evaluated both in vitro assays and nude mice tumor xenograft models, indicating co-targeting EGFR and VEGFR2 may be of clinical relevance in treating EGFR and/or VEGFR2 overexpressing malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Tonra et al used anti-EGFR (cetuximab) and VEGFR-2 (DC101) antibodies in pancreatic (BxPc-3) and colon cancer (GEO) cell lines. The dose response of the combined treatment revealed synergism for both cell lines (CI=0.1, P<0.01 for BxPC-3 and CI=0.1, P<0.01 for GEO) (Tonra et al 2006). Several studies have been conducted using VEGFR-2 inhibitors for treatment highlighting the role of this pathway in the pathogenesis, proliferation and survival of PCa.…”
Section: Clinical Significance Of Targeting Vegfr-2mentioning
confidence: 96%